1998
DOI: 10.1152/ajplung.1998.274.5.l842
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of voltage-gated K+current in rat intrapulmonary arterial myocytes by endothelin-1

Abstract: Although endothelin (ET)-1 is an important regulator of pulmonary vascular tone, little is known about the mechanisms by which ET-1 causes contraction in this tissue. Using the whole cell patch-clamp technique in rat intrapulmonary arterial smooth muscle cells, we found that ET-1 and the voltage-dependent K+(KV)-channel antagonist 4-aminopyridine, but not the Ca2+-activated K+-channel antagonist charybdotoxin (ChTX), caused membrane depolarization. In the presence of 100 nM ChTX, ET-1 (10−10to 10−7 M) caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 41 publications
2
81
1
2
Order By: Relevance
“…The discrepancy between these reports (19) and our data may result from developmental differences between animal models used in these studies (neonatal vs. adult pigs) or the use of endothelin preconstriction in our study. Indeed, endothelin-induced vasoconstriction is mediated in part via K V -, K Ca -, and K ATPchannel inhibition (25,26,35), as is likely the case with most vasoconstrictors (29). Our data suggest that adenosine may overcome the endothelin-mediated inhibition of K V but not K ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between these reports (19) and our data may result from developmental differences between animal models used in these studies (neonatal vs. adult pigs) or the use of endothelin preconstriction in our study. Indeed, endothelin-induced vasoconstriction is mediated in part via K V -, K Ca -, and K ATPchannel inhibition (25,26,35), as is likely the case with most vasoconstrictors (29). Our data suggest that adenosine may overcome the endothelin-mediated inhibition of K V but not K ATP channels.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive studies on the biochemical/physiological role of PKC over several decades have revealed that PKC activation closely linked to cell growth, cell cycle, differentiation, hormone release, reactive oxygen species (ROS) generation, and ion channels modulation (16)(17)(18)(19). Thus, PKC inhibitors are indispensable for studies on PKC-related signaling pathways.…”
Section: Biological Actions Of Pkc Inhibitors On Ion Channelsmentioning
confidence: 99%
“…For example, PKC activation leads to the activation of L-type Ca 2+ channels, Cl − channels, and nonselective cation channels in vascular smooth muscle (20)(21)(22). Generally, K + channels in vascular smooth muscle, including voltage-dependent K + (Kv), ATP-sensitive K + (KATP), and inward rectifier K + (Kir), are inhibited by PKC activation (18,23,24). However, several PKC inhibitors are known to directly affect the ion channels independently of PKC-related signaling pathways, making it difficult to right interpretation of the experimental results.…”
Section: Biological Actions Of Pkc Inhibitors On Ion Channelsmentioning
confidence: 99%
“…The same group, however, also showed that Kv channel inhibition by thromboxane A2 is mediated by the activation of PKCζ (Cogolludo et al, 2003;Ko et al, 2008). Regarding the inhibitory effects of endothelin-1 on pulmonary Kv channels, both Ca 2+ -dependent and -independent subtypes of PKC are involved (Shimoda et al, 1998) (Fig. 2).…”
Section: Effects Of Vasoconstrictors On Kv Channel In Pasmcs: Role Ofmentioning
confidence: 99%